Corpus linguistico e a aquisicao de falsos cognatos em espanhol como lingua estrangeira - Alonso, Maria Cibele Gonzalez Pellizzari (2006)
The main aim of this study was the use of Corpus Linguistics to design teaching material for Brazilian students learning Spanish as a foreign language. Corpus Linguistics is an area of linguistic studies dedicated to the collection and exploration of computer corpora, i.e., large electronic collections of linguistic data carefully collected that form the basis of language or linguistic variety. More specifically, the study presented here was motivated by the necessity of offering one alternative to the learning of false cognates to my Spanish students and teachers and authors of foreign language materials. The principal aim is to focus on the false cognates in Spanish. This was done from the point of view of Brazilian students, since the majority of materials merely cite false cognates. In this study we analyzed the most important patterns of the 10 most frequent false cognates taken from a vocabulary list derived from the analysis of 4 Spanish as foreign language books. From the description of these patterns, we prepared teaching activities. The research questions investigated in the study are: (1) What are the most important patterns of each false cognate? (2) What are most frequent meanings of the false cognates? (3) How can a linguistic corpus help to solve the linguistic interference caused by false cognates? The corpus used in this study was CREA Reference corpus of actual Spanish from Spanish Real Academic, with 160 million words approximately. The analysis showed that a simple translation of false cognates was not enough to enable to their adequate acquisition; we tried to show students the different possibilities of use that false cognates have in context. The activities we suggested are an alternative to learning/teaching that can be adapted to the communicative approach. They can also facilitate discovering process and problems solution, considering that the student is able to build his own knowledge. The study presented here will hopefully have made a contribution to teaching Spanish as a foreign language from Corpus Linguistics perspective, helping to close the gap between Spanish Language teaching in the Brazilian context and Corpus based classroom materials